Perancangan Sistem Pengelolaan Untuk Optimalisasi Stok dan Penjualan Barang di Toko Bahan Bangunan Berkah Balikpapan - Putri Setyaning Astuti; Prasis Damai Nursyam Hamijaya (MANABIS: Jurnal Manajemen dan Bisnis, 2024)
Every business unit has or is currently facing challenges in managing their business, including the Berkah Balikpapan Building Materials Store which is currently facing business problems in managing stock and selling goods. Systems that have not been integrated cause inaccurate data, excess inventory, and decreased customer satisfaction, so risk management solutions are needed to optimize store performance. So this research aims to analyze and optimize the stock management system and sales of goods at the Berkah Balikpapan Building Materials Store using a risk management approach. The method used in this research is direct observation and interviews. Risk analysis is carried out through the use of problem trees to identify three main risk categories, namely operational risk, policy risk and financial risk. The results of the assessment show that policy risk has the highest risk level with a score of 12, which is included in the medium category. Implementing an integrated management system has a positive impact on store performance, including increasing stock data accuracy, reducing excess inventory, and increasing customer satisfaction. Recommendations for handling risks include implementing double verification, regular audits, using automatic monitoring technology, regular training for teams, and preparing detailed contingency plans to reduce the risk level to the low category.